SYNTHESIS AND MORPHOLOGICAL CHARACTERIZATION OF ZNO NANOTUBES ON SUBSTRATES OF GLASS AND SNO 2 :F - Alarcón, Julio (2016)
In this paper the synthesis and morphologic characterization of ZnO nanotubes, made from zinc oxide seed produced by the spray pyrolysis method is reported. The growth of nanotubes of ZnO was conducted by dipping the substrate with a ZnO seed aqueous solution of zinc nitrate and methenamine. The samples manufactured under different conditions were analyzed in morphology by Scanning Electron Microscopy.